Health Risk Analysis and Heavy Metals Speciation of Arable Farmlands In some selected Areas of Northern Taraba State Nigeria - Habibu, Bilyaminu; Olawale, Otitoju; Ejeh, Yakubu Ojochenemi; Umaru, Isaac John; Oko, John Odiba; Yusufu, Dawoye; Dauda, Mai-anguwa Abdulrashid (Darul Yasin Al Sys, 2024)
Background and Objective: Soil plays a major role in food safety and security. A major problem in most developing nations is a lack of food security and safety. The soil environment is a reservoir of nutrients as well as pollutants. This study eval_uated the health risk and heavy metals speciation of arable farmlands in Ardo-Kola, Zing and Yorro, Local Government Areas of Taraba State, Nigeria. Methodology: Three different soil samples from three Local Government Areas of Taraba State (Ardo-Kola, Zing and Yorro) were collected using sterile glass sample collection bottles measured at 5 cm depth. The collected soil samples were freed from unwanted materials by hand picking and air-dried for 5 days to remove excess moisture. The dried soil samples were crushed in with mortar and a pestle, the crushed soil sample was sieved through a 2 mm sieve made of stainless steel the sieved soil sample was further pulverized to a fine powder and passed through a 0.5-mm sieve. Heavy metals (Pb, Cd, Cr, Hg and As) concentrations were assayed using Atomic Absorption Spectrophotometry (AAS). Results: The results showed that Chromium had a high concentration with values ranging from 1.83 mg/kg to 2.62 mg/kg. While Lead and Mercury had the lowest concentration of less than 0.03 mg/kg across the studied areas. For ecological risk assessment parameters; target cancer risk, hazard index (HI) estimated daily intake (EDI) were all determined to assess the non-carcinogenic health risk. Ardo-Kola recorded the highest levels of HM, followed by Yorro, whereas Zing had the lowest concentration. Consumption of crops harvested from the sampled location may pose a serious health challenge; bio-accumulation of toxicants in the soil across the studied areas may pose a health risk due to high concentration of heavy metals which are known to generate free radicals that may lead to oxidative stress and other cellular damages in humans. Conclusion: Although most of the studied heavy metals were significantly present in all the analyzed soil except lead and mercury, their concentration in various soil samples across the studied areas exceeded the permissible levels as recommended by WHO except for Lead and mercury.